Postpartum Care for Women with Gestational Diabetes. Issue 2 (March 2016) - Ortiz, Felina Mychelle; Jimenez, Elizabeth Yakes; Boursaw, Blake; Huttlinger, Kathleen
Abstract: Purpose: To assess postpartum gestational diabetes mellitus (GDM) practice patterns of providers in a large, tertiary care hospital. A retrospective review of medical records for women with GDM receiving postpartum care in 2012 was conducted to estimate the percentage who received a postpartum visit, glucose testing, and preventive follow-up care. Study Design and Methods: A sample of 97 charts was reviewed. Pearson's chi-squared tests and Fisher's exact test were used, as appropriate, to examine differences in documented care by race/ethnicity, insurance type, and type of medical provider. Results: Within the system of study, 53 of 97 women (55%) with GDM had a documented postpartum visit, with disparities by race/ethnicity and insurance type, and 18 (19%) had a documented oral glucose tolerance test after 6 weeks postpartum. Most providers routinely documented interacting with patients around infant feeding, family planning, and emotional status, but fewer documented providing specific care to help patients manage future diabetes risk, with advance practice nurses significantly more likely than physicians to document some aspects of preventive care. Clinical Implications: Postpartum GDM care could be improved by educating providers on the current postpartum GDM standard of care and use of the 5 A's framework for health promotion; prompting providers to order appropriate screenings and document the 5 A's; coordinating follow-up glucose screening and behavioral management with the postpartum visit and subsequent family planning visits; notifying primary care providers and pediatricians of the GDM diagnosis to ensure continuity of care; and referring to allied healthcare providers for intensive behavior change support. Abstract : Gestational diabetes mellitus is one of the most common pregnancy complications in the United States, affecting 7% of all pregnancies, yet care for this population is not always ideal. This study evaluates postpartum care and follow-up for women with gestational diabetes in a tertiary care center in New Mexico.